2022-RA-993-ESGO Comparing thoracic epidural analgesia to surgeon-administered continuous transversus abdominus plane blocks in gynaecologic oncology patients: a retrospective cohort study. (20th October 2022) - Gupta, Vishaal; Drolet, Ann-Rebecca; Matanes, Emad; Power, Joanne; Suarthana, Eva; Gilbert, Lucy; Annie Leung, Shuk On; Zeng, Xing
Abstract : Introduction/Background: Post-operative analgesia comprises of a thoracic epidural (TEA) with multimodal adjuncts. Literature has shown transversus abdominus plane blocks (TAP) offer equivalent analgesia with potential secondary benefits. Our study assessed whether surgeon-administered continuous TAP blocks (cTAP) provided equivalent post-operative analgesia in Gynecologic Oncology patients undergoing abdominal surgery. Methodology: A retrospective cohort study of patients undergoing abdominal surgery at McGill University Health Centre from January 2018–2022 was completed. During the CoVID-19 pandemic, an institutional practice change was made in January 2020 to offer a cTAP with IV rescue patient-controlled analgesia. Patients in the TEA group were treated per standardized Department of Anesthesia protocols. Patients in the cTAP group received a surgeon-administered TAP catheter insertion prior to fascial closure with infiltration of bupivicaine 2–2.5 mg/kg 0.5% diluted 1:1 NS + 10 mg dexamethasone divided bilaterally followed by an infusion of 5–10 cc/hour. Our primary outcome was self-reported pain (numerical rating scale (NRS 0–10)) at 24 h; secondary outcomes included NRS at 1 h, first flatus and bowel movement, vomiting, hospitalization length, and analgesia-related complications. Univariate and multivariate analyses were completed, adjusting for age, body mass index, estimated blood loss, and operative time. Results: Two-hundred forty-four patients met study inclusion criteria: 135 and 109 patients received a TEA and cTAP, respectively. There was no difference in pain scores at 24 h between groups unadjusted (p=0.668) and adjusted (p=0.795 ). The cTAP group had significantly earlier flatus (-0.3 days, p<0.05 ), bowel movement (-0.7 days, p<0.05 ), hospital discharge (-1.4 days, p≤0.05), less vomiting events (OR 0.5 p >0.05 ), and higher NRS at 1 h (1.3, p<0.05 ). The TEA group had more adverse events, hypotension, and inadequate pain control ( p<0.05 ). Conclusion: Our study offers a unique comparison of surgeon-administered cTAP blocks, showing similar analgesic effects with secondary benefits. Further prospective studies are needed to assess utilization of the cTAP block as routine post-operative analgesia.